2016
DOI: 10.4301/s1807-17752016000200001
|View full text |Cite
|
Sign up to set email alerts
|

Learning Management Systems (LMS) and e-learning management: an integrative review and research agenda

Abstract: Information Technology (IT) can be an important component for innovation as enables e-learning and it can provide conditions for an organization to be able to work with new businesses and improved processes. In this regard, Learning Management Systems (LMS) allow communication and interaction between teachers and students in virtual spaces. However, the literature indicates that there are gaps in research, especially concerning the use of IT for the management of e-learning. The purpose of this paper is to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 27 publications
1
57
0
8
Order By: Relevance
“…Fairness (H8) was the only variable that had a weak correlation. These results are consistent with previous studies [52], [70], [91], [94], [95], [97]- [99], [107], [117], [120], [122].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Fairness (H8) was the only variable that had a weak correlation. These results are consistent with previous studies [52], [70], [91], [94], [95], [97]- [99], [107], [117], [120], [122].…”
Section: Discussionsupporting
confidence: 93%
“…Technological characteristics reflect the extent of users' familiarity with technological innovations such as LMS and how well they can adapt to LMS. These characteristics are represented by two variables: control [52], [81]- [86] and attitude [52], [74], [85], [87]- [91]. Mohammadi and Fadaiyan [92] and Piccoli et al [56] found that a user's control over the technology they are dealing with, such as LMS, is directly related to the effectiveness of a learning environment.…”
Section: A: Technological Characteristic Variablesmentioning
confidence: 99%
“…It is better if vital consideration is given to how technology would enable effective integration of LMS, UMIS, resources, communication and social forums. 8 The ICT teams should consider the quality of internet access including the speed or the bandwidth in the design of the virtual school system. Just as critical considerations are given the structure of the physical learning environment, technology and internet quality, strength and compatibility will be crucial to the success of the virtual learning environment.…”
Section: Technologymentioning
confidence: 99%
“…In the context of this study, learning technologies refer to technology innovations that are already mainstream and currently being used to support learning, particularly in higher education (Isaías, 2018). E-learning refers to the use of ICT in the enhancement and support of learning and teaching in education Kalpa Publications in Computing Volume 12, 2019, Pages 123-131 Proceedings of 4th International Conference on the Internet, Cyber Security and Information Systems 2019 (OECD, 2019). TEL extends the application of e-learning, and includes the enhancement of classrooms through learning with technology (Gordon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various trends have shaped learning technologies in the past five years. The wider adoption of Massive Open Online Courses (MOOCs) (Tseng, Tsao, Yu, Chan, & Lai, 2016;Daniel, Cano, & Cervera, 2015), Open Educational Resources (OERs) (Sandanayake, 2019) and Learning Management Systems (LMS) (Oliveira, Cunha, & Nakayama, 2016) have propelled e-learning to be one of the main agenda items for higher education leadership. MOOCs are massive in terms of number of concurrent learners they accommodate, usually for free and delivered online.…”
Section: Introductionmentioning
confidence: 99%